Stateness and sovereign debt Greece in the European conundrum - Lavdas, Kostas A.; Litsas, Spyridon N.; Skiadas, Dimitrios V. (Lexington Books, 2013)
This book examines the present crisis of Greece's political economy as a crisis of stateness, tackling the domestic as well as the international dimensions.